2006
DOI: 10.1016/j.jpsychores.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality is associated with impaired health-related quality of life 7 years following heart transplantation

Abstract: Type D personality is associated with impaired health-related quality of life 7 years following heart transplantation Pedersen, S.S.; Holkamp, P.G.; Caliskan, K.; van Domburg, R.T.; Erdman, R.A.M.; Balk, A.H.M.M. Published in: Journal of Psychosomatic Research Document version:Publisher's PDF, also known as Version of record Publication date: 2006 Link to publicationCitation for published version (APA): Pedersen, S. S., Holkamp, P. G., Caliskan, K., van Domburg, R. T., Erdman, R. A. M., & Balk, A. H. M. M. (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 22 publications
2
29
0
1
Order By: Relevance
“…Classically, the trait models of Eysenck (1991) and of Costa and McCrae (1992) are among those to have received the most research interest. Eysenck's threefactor approach posits that human personality can be encapsulated in the combination of neuroticism, extraversion, and psychoticism, while Costa and McCrae's "big five" swaps psychoticism for openness, agreeableness, and conscientiousness.Recently, however, a personality type known as Type D has shown strong and lasting links to a range of negative health outcomes following coronary events (Denollet, Sys, & Brutsaert, 1995), including death (Denollet et al, 1996), second myocardial infarction (Denollet, Vaes, & Brutsaert, 2000), poor quality of life (Pedersen, Holkamp et al, 2006), and higher rates of depression and anxiety (Denollet, 1998a;Pedersen, Ong et al, 2006). While some have argued that Type D and depression overlap, studies have shown the Type D personality to be an independent predictor of poor coronary outcome, independent of depression (for example, see Schiffer et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Classically, the trait models of Eysenck (1991) and of Costa and McCrae (1992) are among those to have received the most research interest. Eysenck's threefactor approach posits that human personality can be encapsulated in the combination of neuroticism, extraversion, and psychoticism, while Costa and McCrae's "big five" swaps psychoticism for openness, agreeableness, and conscientiousness.Recently, however, a personality type known as Type D has shown strong and lasting links to a range of negative health outcomes following coronary events (Denollet, Sys, & Brutsaert, 1995), including death (Denollet et al, 1996), second myocardial infarction (Denollet, Vaes, & Brutsaert, 2000), poor quality of life (Pedersen, Holkamp et al, 2006), and higher rates of depression and anxiety (Denollet, 1998a;Pedersen, Ong et al, 2006). While some have argued that Type D and depression overlap, studies have shown the Type D personality to be an independent predictor of poor coronary outcome, independent of depression (for example, see Schiffer et al, 2005).…”
mentioning
confidence: 99%
“…Moreover, these two traits themselves appear as though they may overlap with the two traits most prominent in mainstream personality theory, namely neuroticism and extraversion. Although the prognostic power of scores for Type D within cardiac populations is well established (e.g., Denollet, 1998a;Denollet et al, 1995;Denollet et al, 1996;Pedersen, Daemen et al, 2007;Pedersen, Denollet, Ong, Sonnenschein et al, 2007;Pedersen, Holkamp et al, 2006;Pedersen, Ong et al, 2006), virtually none of the research tests whether Type D scores are unique predictors beyond mainstream personality traits.…”
mentioning
confidence: 99%
“…Pederson and colleagues have established a significant negative association between type D personality and impaired QOL in cardiac patients [25]. Similarly have other researchers proven lower health-related QOL in cardiac patients with type D personality trait [26][27][28]. The results of the above-mentioned studies are inconsistent with the results of the present study, which might be due to the fact that patients with type D personality have difficulty in social relations and mostly choose loneliness [29] and patients with breast cancer have additional problems in social relations [4]; thus, they appear less in society and are less affected by the negative feedbacks of the society.…”
Section: Discussionmentioning
confidence: 85%
“…Denollet have previously proposed type D personality and age as independent risk factors for cancer development in men [27]. Carver et al have also associated optimism and psychological well-being to survival of patients with breast cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…sonality가 경험적 근거를 통해 제시되고 있다 (Denollet, 2000(Denollet, , 2005Pederson & Denollet, 2004;Pedersen et al, 2006).…”
unclassified